2011
DOI: 10.1007/s12022-011-9159-6
|View full text |Cite
|
Sign up to set email alerts
|

Value of Ultrasound and Cytological Classification System to Predict the Malignancy of Thyroid Nodules with Indeterminate Cytology

Abstract: Although fine-needle aspiration cytology is considered the gold standard for evaluating thyroid nodules, in about 10-30% of the cases, cytology is indeterminate. This study aimed to determine the value of cytological classification system and ultrasound (US) to predict malignancy in indeterminate thyroid nodule. This retrospective analysis enrolled 80 patients surgically treated at a single center, 75% (60) with benign vs. 25% (20) with malignant lesions at final histology. The clinical, scintigraphic, sonogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 40 publications
5
25
0
Order By: Relevance
“…The second opinion increased the FNAB diagnostic accuracy by 14% and reduced the surgery rate by 25%. Such results demonstrate the importance of cytological review by a pathologist experienced in thyroid surgery recommendations for patients with indeterminate cytology (82,83). …”
Section: Fine-needle Aspiration Cytologymentioning
confidence: 56%
See 1 more Smart Citation
“…The second opinion increased the FNAB diagnostic accuracy by 14% and reduced the surgery rate by 25%. Such results demonstrate the importance of cytological review by a pathologist experienced in thyroid surgery recommendations for patients with indeterminate cytology (82,83). …”
Section: Fine-needle Aspiration Cytologymentioning
confidence: 56%
“…Maia et al (82) evaluated the correlation between the cytological variables of the Bethesda system and clinical, sonographic, and scintigraphic data on indeterminate thyroid nodules. In a sample of nodules with a 25% malignancy rate, category IV of the Bethesda system was an independent predictor of malignancy.…”
Section: Fine-needle Aspiration Cytologymentioning
confidence: 99%
“…This study confirmed a significant increase of risk for malignancy in thyroid nodules with indeterminate cytology showing Bethesda System category IV and suspicious features at US. These findings enhance our current limited predictive armamentarium and can be used to guide surgical decision making [53].…”
Section: Tips and Tricksmentioning
confidence: 68%
“…Many of these studies combine clinical and imaging features in order to predict malignancy (3032). Most of these models rely heavily on ultrasound features such as calcifications, irregular borders, hypoechogenicity, and nodule size.…”
Section: Discussionmentioning
confidence: 99%